2022
DOI: 10.1590/0037-8682-0269-2021
|View full text |Cite
|
Sign up to set email alerts
|

Trend of the Burden of Larynx Cancer in Brazil, 1990 to 2019

Abstract: Introduction: Larynx cancer is one of the most common head and neck cancers, whose main risk factors are smoking and alcohol use, and its occurrence and prognosis depend on adequate and timely preventive measures. This study aimed to investigate the burden of larynx cancer in Brazil and its states. Methods: Using estimates from the Global Burden of Disease Study 2019, this study analyzed the trends of incidence, mortality, and disability-adjusted life years (DALYs) for larynx cancer between 1990 and 2019, besi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Although the burden of laryngeal cancer decreased in Brazil in the studied period, regional inequalities in the country remain evident, especially for men 21 . This study found disparities between Brazilian states, with higher mortality and DALY rates attributable to occupational risk factors from 1990 to 2019 in some Northern and Northeastern states.…”
Section: Discussionmentioning
confidence: 87%
“…Although the burden of laryngeal cancer decreased in Brazil in the studied period, regional inequalities in the country remain evident, especially for men 21 . This study found disparities between Brazilian states, with higher mortality and DALY rates attributable to occupational risk factors from 1990 to 2019 in some Northern and Northeastern states.…”
Section: Discussionmentioning
confidence: 87%
“…Embora tenha sido verificada uma queda na carga de câncer de laringe no Brasil no período estudado, as desigualdades regionais no país permanecem evidentes, principalmente para o sexo masculino 21 . Neste estudo, foram verificadas disparidades entre os estados brasileiros, com aumento das taxas de mortalidade e DALYs atribuíveis aos fatores de risco ocupacionais entre 1990 e 2019 em alguns estados das regiões Norte e Nordeste.…”
Section: Discussionunclassified